Quality of Work Life, Work Life Balance and Psychological Well-Being of Registered Nurses in Medium-Sized Private Hospitals in the Bangkok Metropolitan - แจ้งจิตร์, สุพักตรา; สมุทรานนท์, ทิพทินนา (Journal of The Royal Thai Army Nurses, 2019)
The objectives of this research were to study: 1) the relationship between registered nurses’ quality of work life and work life balance with psychological well-being; and 2) the factors could be jointly predict registered nurses’ psychological well-being in medium-sized private hospitals in the Bangkok Metropolitan. The samples were consisted of 296 registered nurses in medium-sized private hospitals in the Bangkok Metropolitan. Data were collected by questionnaires which consisted of 4 parts: personal factors, quality of work life, work life balance, and psychological well-being. Statistical parameter used in this research were Pearson’s product moment correlation coefficient, and stepwise multiple regression analysis. Results showed that: 1) registered nurses’ quality of work life and work life balance (work/personal life enhancement) were positively related to registered nurses’ psychological well-being and registered nurses’ work life balance (work interference with personal life and personal life interference with work) was negatively related to registered nurses’ psychological well-being and 2) registered nurses’ quality of work life (social integration and growth and security), work life balance (personal life interference with work and work/ personal life enhancement) could jointly predicted 36.20 percentage of registered nurses’ psychological well-being in medium-sized private hospitals in the Bangkok Metropolitan at statistically significance at .01 level.